1998
DOI: 10.1097/00005053-199805000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Center for Epidemiologic Studies Depression (CES-D) Scale in Korea

Abstract: We translated the Center for Epidemiologic Studies Depression (CES-D) Scale into Korean, paying careful attention to culturally different modes of expression of depressive feelings and thoughts. The final translated version (CES-D-K) was administered to 164 psychiatric patients and 464 normal subjects residing in the community. Reliability, validity, and the optimal cutoff point of this scale were estimated, including ROC analysis. The CES-D-K was reliable and valid for the Korean population. Two optimal cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
262
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(267 citation statements)
references
References 23 publications
5
262
0
Order By: Relevance
“…While full analysis of the social significance of certain illnesses is beyond the scope of this paper, see Saint Arnault (in press). the depression scores on a variety of self-report depression screening instruments (Cho & Kim, 1998;Iwata & Buka, 2002;Iwata, Roberts & Norito, 1995;Iwata & Roberts, 1996;Iwata, Saito & Roberts, 1994;Iwata et al, 1998;Noh, Kasper and Chen, 1998). Therefore, the findings reported here may not accurately represent the incidence of depression in the women in these samples because of the avoidance of strong negative and positive emotional endorsement.…”
Section: Discussionmentioning
confidence: 79%
“…While full analysis of the social significance of certain illnesses is beyond the scope of this paper, see Saint Arnault (in press). the depression scores on a variety of self-report depression screening instruments (Cho & Kim, 1998;Iwata & Buka, 2002;Iwata, Roberts & Norito, 1995;Iwata & Roberts, 1996;Iwata, Saito & Roberts, 1994;Iwata et al, 1998;Noh, Kasper and Chen, 1998). Therefore, the findings reported here may not accurately represent the incidence of depression in the women in these samples because of the avoidance of strong negative and positive emotional endorsement.…”
Section: Discussionmentioning
confidence: 79%
“…These findings are in contrast to previous research from Japan 11) , which could be related to cultural differences 30) . Koreans tend to experience difficulty in expressing positive emotions, unlike individuals in other countries; this may be a consequence of Confucian ethics 31) . Therefore, negative emotions can be expressed more easily than positive emotions so that the former are a more precise barometer of elderly functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, negative emotions can be expressed more easily than positive emotions so that the former are a more precise barometer of elderly functional decline. The aforementioned opposing feelings can have different effects on the prediction of functional decline according to ethnicity and culture 31) . Our findings have some important implications.…”
Section: Discussionmentioning
confidence: 99%
“…Cho, Nam, and Suh [1] studied the prevalence of depressive symptoms in Korean adults. They found that 25.3% of Korean adults had depression scores above the cutoff of 16 on the Korean version of the Center for Epidemiologic Studies Depression Scale (CES-D) and 8.6% of those had depression scores above 25 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no study has ever tested this model with South Korean participants. Previous studies have reported the differences in response patterns between American and Korean participants to items on the CES-D [1]. For example, Cho and Kim (1998) reported that Korean participants scored lower on the anhedonia subscale than their American counterparts.…”
Section: Introductionmentioning
confidence: 99%